Komunikasi Penyuluhan Badan Pangan Nasional (BPN) Melalui Ecological Citizenship dalam Mendorong Ketahanan Pangan di Sumatera Utara - Dalimunthe, Maulana Andinata; Habibi, Muhammad Lutfi; Ritonga, Aulia Rahma (Jurnal Kajian Agraria dan Kedaulatan Pangan (JKAKP), 2023)
Food security for a country is a very important thing. Food is a basic need that is essential and very fundamental for humans to fulfill and maintain their life. This study aims to see how extension communication activities are carried out by the National Food Agency (BPN) as part of the government in realizing ecological citizenship and increasing the national food security index. This study uses a case study approach to analyze extension activities carried out by the National Food Agency (BPN) in realizing ecological citizenship and food security. The results of the research show that food security based on three pillars (availability, affordability, utilization) has coherence which basically can be achieved by prioritizing environmental preservation. Extension activities with the concept of ecological citizenship play an important role because they use a bottom-up approach, namely through direct community participation. Through the concept of ecological citizenship, the government does not just solve food security problems, but simultaneously can protect the environment. Optimization of ecological citizenship in increasing national food security is carried out through clear and effective counseling intensity by prioritizing sustainability and humanist principles, such as counseling based on health knowledge, as well as maintenance of an equitable environment.